Kualitas Kerupuk Udang Goreng Dengan Substitusi Tepung Ubi Jalar Selama Penyimpanan Quality Fried Shrimp Chips With Substitution of Sweet Potato Flour During Storage - Linda Kurniawati, Merkuria Karyantina & (Exsplorasi, 2011)
ABSTRACTNutritions of fried shrimp chips can improve with sweet potato floursubstitution. Weakness the chips are lost of crispy during storage, it can inhibit with sweet potato flour substitution which can bind water content. Object this research are to observe quality of fried shrimp chip s during storage, which making from shrimp waste and sweet potato flour substitution . The product storage in room temperature. Research design was faktorial complete random sampling with 2 factor : sweet potato flour substitution level (0%, 10% and 20%) and days of storage (14, 21 and 28 days). Parameter research are moisture content, ash content and beta carotene level. Result showed moisture content during storage had tendency to increase; sweet potato flour substitution showed various tangible toward moisture content of fried shrimp chips. Increasing of sweet potato flour substitution, ash content would tangible effect toward ash content dan beta carotene level.Highest of beta carotene level on shrimp chips with sweet potato flour substitution 20% per gram of dough with 2 week storage, and so long storage beta carotene level had decrease. Fried shrimp chips can consume until 28 days of storage and beta carotene level are high.Keywords : shrimp chips, sweet potato, storage